Technology-Based Theological Training Answers The Challenges Of The Times - Samuel Elkana (International Perspectives in Christian Education and Philosophy, 2024)
This study examines how technology-based theological training can answer the challenges of an era that is increasingly influenced by the rapid development of digital technology, especially in the context of theological education at the Kerusso Theological College (STT). The urgency of this study lies in the need for a new approach to theological training that not only focuses on doctrinal and practical aspects, but also integrates technological mastery to prepare students for the digital era. With technology-based training, STT students can be better prepared to serve and convey the Gospel message effectively amidst the dynamic changes of the times.The main objective of this study is to explore how technology-based theological training affects students' competence in responding to the challenges of modern evangelism missions, as well as to identify strategies that can be implemented to increase the effectiveness of delivering the gospel message. This study uses a qualitative method with an in-depth interview approach and document analysis related to the curriculum and training activities at STT Kerusso. The data obtained were analyzed descriptively to see patterns of technology implementation in theological training and its impact on students' readiness to serve in the midst of a digital society.The results of this study are expected to contribute to the development of the curriculum in theological educational institutions, as well as being a reference for other theological institutions in utilizing technology as a holistic and contextual training tool. These findings are also expected to help theological institutions in designing relevant and applicable training to prepare a generation of servants who are able to answer the challenges of the times.